The Concept of Time and Space on the Internet Analyzed through the Pseudonymous (International Journal of Engineering and Computer Science, 2015)
If the digital society is rooted in civil society, it does not duplicate. Indeed, a great number of social practices are put into place both in the real world as well as in the virtual world and are organized around the same objects: time and space; however, they differ in their realization. The Internet is at the crossroads of two phenomena that oppose one another with respect to both their concepts and the social practices involved; these are anonymity and privacy life. Quite clearly a number of phenomena have emerged from these different Internet approaches. So, what are the consequences of these new concepts of time and space on Internet?